PP.17.19: EFFECTS OF CALCIUM CHANNEL BLOCKADE, ANGIOTENSIN CONVERTING ENZYME INHIBITION AND THEIR COMBINATION ON 24 HOUR BLOOD PRESSURE MEAN AND VARIABILITY IN ELDERLY HYPERTENSIVE PATIENTS. (June 2015) - Parati, G.; Castiglioni, P.; Faini, A.
Abstract : Objective: Evidence is available that increased 24 h blood pressure (BP) variability (V) contributes to organ damage and cardiovascular events rate in hypertension, independently from BP levels. Limited information is available however on the effects of different monotherapies and of drug combinations on 24 h BPV. Aim of this work was to explore the effects on 24 h BP mean values and on BPV of monotherapies with a calcium antagonist (Lercanidipine, L) or an ACE inhibitor (Enalapril, E), and of their combination. Design and method: 67 hypertensives (age 60–85yrs) received 4-week treatments with L (10 mg), E (20 mg), their combination (L10+E20) or placebo (P) in a randomized order. 24 h ambulatory BP recordings were performed at the end of each treatment. 24 h average systolic (S) and diastolic (D)BP levels were computed, and BPV was quantified as 24 h weighted standard deviation (SDw) and as average real variability (ARV) for SBP and DBP. The dependence of changes in BPV on changes in average BP was tested by linear regression analysis. Results: When comparing monotherapies, E produced a larger decrease in average 24 h SBP and DBP than L, the largest reduction being induced by L+E. 24 h short term BPV was best reduced by L+E, especially for DBPV. L induced a larger decrease in 24 h DBPV than E, the effect being more evident for ARV (table). No significant correlation was found between the reduction in average mean BP levels and the concomitant reduction in 24 h BP standard deviation for all treatments (R2 always <0.09, p = NS). Figure. No caption available. Conclusions: L+E combination reduced average 24 h SBP and DBP more effectively than the respective monotherapies, with E being slightly more effective than L in reducing BP levels. Short term SBPV was significantly reduced only by L+E in particular when assessed as AVR. The reduction in short term DBPV was more pronounced, independent from the reduction in average BP levels, maximal with combination treatment and more evident with L than with E. These results may have implications for cardiovascular protection when selecting antihypertensive drugs in elderly hypertensive patients, and further support the efficacy of calcium channel blockers in reducing BPV.